2021
DOI: 10.1007/s11896-020-09425-8
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Biases in Criminal Case Evaluation: A Review of the Research

Abstract: Psychological heuristics are an adaptive part of human cognition, helping us operate efficiently in a world full of complex stimuli. However, these mental shortcuts also have the potential to undermine the search for truth in a criminal investigation. We reviewed 30 social science research papers on cognitive biases in criminal case evaluations (i.e., integrating and drawing conclusions based on the totality of the evidence in a criminal case), 18 of which were based on police participants or an examination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…To the best of the authors' knowledge, we are the first to review this topic using a systematic literature review (SLR). The existing review studies have concentrated on a topic such as cognitive biases in criminal cases (Meterko & Cooper, 2021) and criminal deterrence (Chalfin & McCrary, 2017). Following the SLR process applied in several studies (i.e., Khatib et al, 2022;Sahi et al, 2021), a final set of 114 articles was included in this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, we are the first to review this topic using a systematic literature review (SLR). The existing review studies have concentrated on a topic such as cognitive biases in criminal cases (Meterko & Cooper, 2021) and criminal deterrence (Chalfin & McCrary, 2017). Following the SLR process applied in several studies (i.e., Khatib et al, 2022;Sahi et al, 2021), a final set of 114 articles was included in this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological and criminological researchers have continuously sought to comprehend countless interacting biological, psychological, and social factors to clarify why some people tend to involve in criminal and antisocial behaviors ( 1 ). Numerous theories attribute the basis of these behaviors to factors such as personality ( 2 ), mental disorders ( 3 ), ineffective parenting ( 4 ), cognitive factors and skills ( 5 ). Also, numerous studies have revealed that men are more prone to criminal and anti-social behaviors compared to women ( 6 , 7 ).…”
mentioning
confidence: 99%
“…Based on REBT, antisocial behaviors can also be influenced by errors in habits and thoughts. The result of a study by Meterko and Cooper (2021) also indicates that cognitive bias is one of the causes of people's tendency towards criminal and anti-social behavior ( 5 ).…”
mentioning
confidence: 99%
“…Thus, it is a target that must constently be pursued, although it can never be fully reached let alone be secured permanently. There is a profound and growing body of literature (e.g., [ [1] , [2] , [3] , [4] , [5] , [6] , [8] , [9] ]; for Refs. see also [ 10 ] on how to identify, manage and potentially reduce bias.…”
mentioning
confidence: 99%